Edukasi Penanganan Fraktur Ekstremitas Untuk Pasien di Semarang RSD K.R.M.T Wongsonegoro: Extremity Fracture Handling Education for Patients at Semarang City Hospital - Puspitaningtyas, Dyah Ayu; Ridwan, Achmad; Kuncoro, Ignasius Dwi (J.Abdimas: Community Health, 2024)
There are some people who still have no idea how to properly treat fractures in the modern era. or contemporarily using the latest technology. One way to handle fractures that uses radiology technology. The aim of this community service is to increase knowledge about fracture management. Methods This community service involved demonstration and distribution of questionnaires. This was followed by distributing leaflets to provide a summary of the material. With 20 participants, the community service was conducted on June 12-13, 2023. The background of the counseling participants consisted of families of patients from various age groups and genders. The results showed that almost 95 percent of the participants had insufficient knowledge about the types of fracture treatment with a good knowledge category. In contrast, the results after demonstration, leaflet, and questionnaire refilling showed that almost 95 percent of the participants did not understand about fracture management with poor knowledge category. It can be concluded that this activity is expected to provide new knowledge to patients and their families and improve services at Semarang City Hospital.